Therapeutic strategies targeting inflammation and immunity in atherosclerosis: how to proceed? - Engelen, SE; Robinson, AJB; Zurke, Y-X; Monaco, C (Springer Nature, 2022)
Atherosclerosis is a chronic inflammatory disease of the arterial wall, characterized by the formation of plaques containing lipid, connective tissue and immune cells in the intima of large and medium-sized arteries. Over the past three decades, a substantial reduction in cardiovascular mortality has been achieved largely through LDL-cholesterol-lowering regimes and therapies targeting other traditional risk factors for cardiovascular disease, such as hypertension, smoking, diabetes mellitus and obesity. However, the overall benefits of targeting these risk factors have stagnated, and a huge global burden of cardiovascular disease remains. The indispensable role of immunological components in the establishment and chronicity of atherosclerosis has come to the forefront as a clinical target, with proof-of-principle studies demonstrating the benefit and challenges of targeting inflammation and the immune system in cardiovascular disease. In this Review, we provide an overview of the role of the immune system in atherosclerosis by discussing findings from preclinical research and clinical trials. We also identify important challenges that need to be addressed to advance the field and for successful clinical translation, including patient selection, identification of responders and non-responders to immunotherapies, implementation of patient immunophenotyping and potential surrogate end points for vascular inflammation. Finally, we provide strategic guidance for the translation of novel targets of immunotherapy into improvements in patient outcomes.